Structural Insufficiency Anomalies in Cardiac Valves - Kirali, Kaan (IntechOpen, 2018)
Heart valves are the basic functional structure of the heart to obtain, sustain, and maintain blood circulations in the body without energy loss, allowing blood regurgitation or obstructing blood flow. There are two basic designs of heart valves: actively protected via subvalvular apparatus (atrioventricular valves) and passively strengthened (ventriculoarterial valves). The embryologic and morphologic development of heart valves is the key stage to continue normofunctional structure and physiological behavior. Fetal anomalies, embryologic defects, or non-development pathologies may damage the structure of heart valves and cause functional deterioration at different grades. In this book, we have focused on specific pathologies, which require special knowledge and treatment modalities.